2022
DOI: 10.1097/tp.0000000000003961
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Donor Seropositivity Negatively Affects Survival After Heart Transplantation

Abstract: Background. Prior studies have shown that cytomegalovirus (CMV) infection is a risk factor for the development of cardiac allograft vasculopathy (CAV) and is associated with reduced long-term survival after heart transplantation (HTx). The aim of this International Society for Heart and Lung Transplantation Transplant Registry study was to compare posttransplant survival in different CMV donor:recipient serologic combinations. Methods. We performed a retrospective cohort study, using the International Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…We did not specifically assess patient outcomes in this cohort, but the association between CMV D+R-status and worse allograft and patient survival has been previously well-established across multiple organ types. [1][2][3][4] In summary, our study demonstrated that the proportion of high-risk CMV D+R-SOTs has increased significantly from 2000 to 2020, most notably among liver, heart, and lung SOTs, and is projected to be >25% among nonkidney SOTs by 2040 if current trends continue. This increase in the proportion of D+R-SOTs appears to be driven largely by decreasing CMV seroprevalence among candidates rather than increased seroprevalence among donors.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We did not specifically assess patient outcomes in this cohort, but the association between CMV D+R-status and worse allograft and patient survival has been previously well-established across multiple organ types. [1][2][3][4] In summary, our study demonstrated that the proportion of high-risk CMV D+R-SOTs has increased significantly from 2000 to 2020, most notably among liver, heart, and lung SOTs, and is projected to be >25% among nonkidney SOTs by 2040 if current trends continue. This increase in the proportion of D+R-SOTs appears to be driven largely by decreasing CMV seroprevalence among candidates rather than increased seroprevalence among donors.…”
Section: Discussionmentioning
confidence: 70%
“…We did not specifically assess patient outcomes in this cohort, but the association between CMV D+R– status and worse allograft and patient survival has been previously well-established across multiple organ types. 1-4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous calls have been made 10 , 41 , 42 for actions to mitigate the impact of CMV on post-SOT. In addition to the aforementioned approaches, several prevention measures have been proposed.…”
mentioning
confidence: 99%
“… 15 , 16 , 32 , 40 , 43 , 44 This article focuses on one such proposal: CMV serological matching while allocating deceased donor organs. 10 , 16 , 17 , 45 CMV matching has been advocated and practiced as early as 1988 in the United States 46 and the United Kingdom, 47 , 48 despite some contradictory findings. 15 , 30 , 35 , 42 , 49 A recent U.S. pilot study 16 documented that successful CMV matching is possible without adversely affecting local transplant rates and waitlisted times.…”
mentioning
confidence: 99%